Internalized equality and protest against injustice: The role of disadvantaged group members’ self‐respect in collective action tendencies - Renger, Daniela; Eschert, Silke; Teichgräber, Mimke L.; Renger, Sophus (European journal of social psychology, 2020)
Recent research shows that self‐respect (defined as seeing yourself as a person with equal rights) predicts assertive but not aggressive responses to injustice in interpersonal contexts. The present research focuses on the antecedents of self‐respect and its consequences for collective action tendencies among members of disadvantaged groups. Across three studies (N = 227, N = 454, N = 131) using different contexts and samples (discrimination of Muslims in Germany; women regarding gender inequality), experiences with equality‐based respect (defined as being treated as someone of equal worth) predicted self‐respect. Moreover, across all three studies, self‐respect predicted intentions for cooperative or normative but not support for hostile or non‐normative protest. The results demonstrate the potential of self‐respect for facilitating collective action in the face of injustice while still enabling positive intergroup relations.